Chrystus jako kaznodzieja łaski w posłudze przepowiadania kapłanów - Nawracała, Tomasz (Poznańskie Studia Teologiczne, 2022)
The preaching of the word of God is among the primary tasks and duties of those elected to the ministerial priesthood. The ministry of the word aims at awakening faith in the hearers or at strengthening it. This action, however, does not depend solely on the preacher of the word, but is first an effect of God’s action. God acts constantly through His living words, which, adapted to man’s capacity, become the source of faith in him, that is, of the reception of revelation in its definitive form. Faith already gives man a certain, albeit limited, share in eternal life, and preaching ultimately aims to fulfil God’s desire: that all may be saved. What makes the preaching of the word of God still effective even after two thousand years? That is the question this article discusses, pointing out that this effectiveness depends on a double concomitance between the divine and the human: one in the preacher and the other in the hearer.